Práticas de tecnologia social de uma associação comunitária - Dalbem, Diego Martins (2019)
This study discusses the Social Technology practices of a Santa Catarina Community Association, namely the Taquaras District Community Association (ACDT). To this end, it analyzes the theoretical spectra of Social Technology (TS) and Community. Based on the writings of authors that make up the Social Technology Network (RTS), the Social Technology categories were defined for scrutiny of the ACDT community experience. The categories are: 1) Reason for being; 2) Decision making processes; 3) The role of the population; 4) systematic; 5) Knowledge building; 6) Sustainability; and 7) Scale up. The methodology used was the qualitative case study, with descriptive approach, from the literature review. The research instruments have semi-structured and documentary interviews with ACDT managers and associates. Data analysis and interpretation were performed through the historical and cultural contextualization of Taquaras District and the 7 categories indicated. Among the results, it was possible to observe that the association under study is composed of a large part of the community, which actively participates in the activities and, therefore, in the daily life of the association. From the analysis of the existing literature on the subject and as revealed by the presence (to a greater or lesser extent) of the seven constituent elements of the TS, the practice of Social Technology in the ACDT community actions was evidenced. This point reinforces the particularities of Social Technology as innovative and inclusive knowledge and action and suggests, from the research point of view, further studies regarding the experiences of community associations that develop Social Technology.